Sistema de gestão de energia otimizado para maximização do lucro de uma usina fotovoltaica com baterias aplicado ao mercado de curto prazo - Oliveira, Liane Marques de (2024)
Photovoltaic (PV) generation plants, due to the intermittent nature of their output power, can benefit from the integration of battery energy storage systems (BESSs). In this context, this work proposes an optimized energy management system (EMS) for a joint operation of BESS in utility-scale PV plants (PV/BESS) aiming to profit maximization. The optimization of the BESS operation was achieved from the genetic algorithm, and for the problem formulation, the following cost functions were defined in the objective function: the energy pricing system; the costs associated with degradation and total loss of the batteries; the penalty related to exceeding the maximum power contracted. The proposed EMS defines the reference for a BESS to be integrated into a PV plant located in Coremas, Brazil. The results were obtained from a simulation architecture similar to the PV plant and demonstrated positive financial gains, compared to the operation of the PV plant without BESS. In the simulation of a whole year of operation, it was possible to achieve an additional daily revenue gain of up to 11% and the return on investment obtained was 10 years and 3 months.